BALANCE EXERCISE UNTUK MENCEGAH KEJADIAN JATUH PADA LANSIA - Iswati Iswati (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2020)
Background. Fall incident is one of the problems that often occurs in the elderly. The falling event occurs because of decreased strength in the lower extremity muscle. The elderly need balance exercises to increase muscle strength and improve body balance. The Aim of The Study. To Analyze the effect of balance exercise on falling events in the elderly. Subject and Method. The research method used is quasi experimental. The population of 60 elderly with 52 samples was divided into 26 elderly in the intervention group and 26 elderly in the control group. The sampling technique is purposive sampling. The measuring instrument used is the fall event questionnaire and the Breg Balance Scale observation sheet, nominal data scales using McNemar and Chi-Square data analysis techniques. Result. McNemar and Chi-Square statistical test results show the value of p = 0,000 with a significance value Î± <0.05. Conclusion. There is an effect of balance exercise on the incidence of falls in the elderly.Keywords: balance exercise, elderly, fall eventsKorespondensi: Iswati. Program Studi D3 Keperawatan STIKES Adi Husada, Jln. Kapasari 95 Kota Surabaya, Jawa Timur. Email: iswatisaja@gmail.com